DEVELOPMENT OF MODERN PREVENTIVE PROGRAMS IN ORTHODONTIC TREATMENT OF DENTAL CARIES IN CHILDREN ON THE BASIS OF HYGIENIC REQUIREMENTS - Rizayeva Sevara Mirgulamovna; Fozilov Uktam Abdurazzakovich (International Engineering Journal For Research & Development, 2020)
In the world of orthodontic treatment, a large-scale scientific study is being carried out to forecast and determine the early symptoms of caries in children, as well as to optimize the effectiveness of diagnostic and therapeutic-prophylactic measures, the existing methods of diagnosis are no longer sufficient, there has been a persistent need for additional methods of research. In this regard, the study of diagnostic and therapeutic measures aimed at increasing the quality indicators of orthodentic care for children is Perspektiv.In the early stages, during orthodentic treatment, it is necessary to diagnose caries and develop the maximum possible concomitant treatment, to obtain a stable aesthetic result in the treatment of orthodentic patients, and to avoid relapses, it is possible..